Hubungan Ekspresi Cyclooxygenase-2, Reseptor Estrogen dan Derajat Histologi Invasive Carcinoma of No Special Type Payudara - I Nyoman Upadana; I Gusti Alit Artha (Majalah Patologi Indonesia, 2015)
Background Cyclooxygenase-2 (COX-2) overexpression clearly plays an important role in the pathogenesis of breast cancer. The relationship between COX-2 expresion with histological grade and estrogen receptor (ER) in invasive carcinoma NST of the breast remains uncertain. The aim of this study was to evaluate the correlation between expression of COX-2 and ER with histology grade of invasive carcinoma NST of the breast. Methods This is observasional analitik cross-sectional study, the histology grade was assessed on by hematoxillin eosin, COX-2 and ER expression was assessed by immunohistochemistry (IHC) staining. The correlation between COX-2 and ER expression with histological grade were analysed by Pearson Chi-Square. Results 60 samples were studied, the youngest case was 28 years old and the oldest case was 79 years old. According to histological grade we found the case of low grade were 27 cases (45%) and high grade were 33 cases (55%). COX-2 expression positif was found in 53.4% and was correlated to histological grade (p=0.045), however between ER expression and histological grade, and COX-2 expression and ER expressionere not correlated. Conclusion COX-2 expression has correlation with histological grade, and COX-2 expression was not correlated with ER expression, and ER expression was not correlated with histological grade invasive carcinoma NST of breast. Key words : COX-2,ER, histologic grade, invasive carcinoma NST of Breast.